The Nature of and Conditions for Online Trust - Koehn, Daryl (Journal of business ethics, 2003)
As use of the Internet has increased, many issues of trust have arisen. Users wonder: will my privacy be protected if I provide information to this Internet vendor? Will my credit card remain secure? Should I trust that this party will deliver the goods? Will the goods be as described? These questions are not merely academic. A recent Boston Consulting Group study revealed that one out of ten consumers have ordered and paid for items online that never were delivered (Williams, 2001). This year consumers filed around 11,000 complaints with the Federal Trade Commission alleging auction fraud, a figure up from the 107 lodged in 1997. It is no wonder that people are increasingly worried about whom to trust in online interactions. This paper explores the conditions under which online trust thrives and looks at examples of best and worst corporate practices. Online trust issues arise in a wide array of forums – chat rooms, news postings, e-catalogues, and retail transactions, to name a few. This paper focuses primarily on the online retail market, but the analysis applies to informational and entertainment sites as well.